Spark plasma texturing: A strategy to enhance the electro-mechanical properties of lead-free potassium sodium niobate ceramics. (June 2020) - Pinho, Rui; Tkach, Alexander; Zlotnik, Sebastian; Costa, M. Elisabete; Noudem, Jacques; Reaney, Ian M.; Vilarinho, Paula M.
Graphical abstract: Abstract: Controlling the sintering and microstructure of lead-free potassium sodium niobate ((K1-x Nax )NbO3, KNN) ceramics is of primary importance to optimize its piezoelectric / ferroelectric properties. However, sintering dense and monophasic KNN remains a challenge. Here, we prepare KNN ceramics using spark plasma texturing (SPT), a modified spark plasma sintering (SPS) technique, in which uniaxial pressure is applied in an edge-free configuration, allowing ceramics to deform in the radial direction. Densification at low temperatures (1000 °C) and for short times (20 min) is achieved by SPT accompanied by constrained grain growth (average grain size = 1.4 μm), resulting in enhanced piezoelectric properties ( d33 = 108 pC N −1 and g33 = 21.2 × 10 −3 Vm N −1 ). In addition, and of relevance, SPT KNN ceramics reveal a more homogeneous electrical microstructure postulated to be related with a reduced diffusion and local segregation of defects, resulting in grain cores and shells with more similar capacitances and conductivities. Our work brings new practical understanding to sintering of KNN and demonstrates the potential of alternative densification strategies for improved lead-free dielectrics.